Households' response to the wealth effects of inflation - Philip Schnorpfeil; Michael Weber; Andreas Hackethal (Leibniz Institute for Financial Research SAFE, 2023)
We study the redistributive effects of inflation combining administrative bank data with an information provision experiment during an episode of historic inflation. On average, households are well-informed about prevailing inflation and are concerned about its impact on their wealth; yet, while many households know about inflation eroding nominal assets, most are unaware of nominal-debt erosion. Once they receive information on the debt-erosion channel, households update upwards their beliefs about nominal debt and their own real net wealth. These changes in beliefs causally affect actual consumption and hypothetical debt decisions. Our findings suggest that real wealth mediates the sensitivity of consumption to inflation once households are aware of the wealth effects of inflation.
Keywords: D12; D14; D83; D84; E21; E31; E52; 330; Inflation Beliefs; Information Treatment; Consumption; Monetary Policy